Computational study on 1D quantum spin chain - Chung, Jia Hui (Nanyang Technological University, 2023)
Due to the large quantum fluctuation, there are many 1D quantum magnets in real life which exhibit exotic phases, such as quantum spin liquid state in the ground state of Cs4CuSb2Cl12 and PbNi2V2O8 [2] and SrNi2V2O8 [3] whose ground state is close to the phase boundary between Haldane phase (which is a fourfold-degenerate edge state) and Ising antiferromagnetic phase.